Determinants and managerial trustworthiness in the capital structure and debt maturity: Evidence from Shariah compliant and conventional firms in Pakistan / Naveeda Akhter Katper - Naveeda Akhter , Katper (2018)
The emergence of Shariah compliant firms is gaining attention in the financial markets. Inspired by the role of trustworthiness as a catalyst to minimize the rift between the interest of management and ownership, the study examines the impact of managerial behaviour on Shariah compliant and conventional firm’s corporate financing decisions under the aegis of modern agency cost theory. The study argues that since the shariah compliant and conventional firms are expected to follow the entirely different philosophy of doing business, this might be reflected in their financial decisions. Thus, the study seeks to establish a relationship between corporate decisions and Shariah principles covering the areas of the capital and debt maturity structure in relation to the ownership structure. In brief, the study has four main objectives including (a) investigating the determinants of capital structure in the Shariah and conventional firms, (b) probing the managerial trustworthiness or self-interest in the capital structure decisions of the Shariah-compliant and conventional firms, (c) examining the determinants of debt maturity structure in the Shariah-compliant and conventional firms, and (d) examining the managerial influence in the decision of debt maturity choice in the Shariah-compliant and conventional firms. The sample firms consist of 68 Shariah compliant firms and 75 conventional firms from the listed companies on Pakistan Stock Exchange (PSX) of Pakistan for the period of five years from 2009 to 2013. Data analysis is carried out using different statistical and econometric methods including the univariate and multivariate techniques. The study applies t-test, pooled regression, Fixed and Random effects, Tobit regression, and robust regression M- estimation. The study extends the analysis at the sector-level. Results show some significant variations among the impact of various determinants of leverage and debt maturity among the Shariah and conventional firms. Our most striking finding is that the debt maturity among Shariah firms is significantly shorter than conventional firms. With regards to trustworthiness, results show that, unlike conventional firms, leverage ratios in Shariah firms are insensitive to the varying degree of managerial ownership, indicating the absence of managerial opportunism in financial decisions of these firms. For the conventional firms, however, the results confirm findings of previous research which reveal that managers manipulate leverage ratios in their own interest at the cost of shareholders and firm value, indicating the severity of agency conflicts among these firms. Invoking agency theory, the study suggests that certain firm characteristics (such as lower free cash-flows and lesser liquidity), achieved through Shariah compliance, help Shariah firms mitigate agency conflicts. These features persuade managers to behave less opportunistically than their counterparts in conventional firms as shown from their financing choices. Amid the dearth of studies investigating the relationship between Shariah compliance and firm’s choice of financial decisions, our study would be a source of unfolding the debate and understanding the nature of capital and debt maturity structure of Shariah firms. The research findings are also expected to benefit large and growing clientele of the Shariah firms by providing better insights on the capital and debt maturity structure of these firms.